Solve (x + 3)2 + (x + 3) – 2 = 0. Let u = Rewrite the equation in terms of u. (u2 + 3) + u – 2 = 0 u2 + u – 2 = 0 (u2 + 9) + u – 2 = 0 u2 + u + 1 = 0 Factor the equation. What are the solutions of the original equation?

Respuesta :

Answer:

The solutions of the original equation are x=-5 and x=-2

Step-by-step explanation:

we have

[tex](x+3)^2+(x+3)-2=0[/tex]

Let

[tex]u=(x+3)[/tex]

Rewrite the equation

[tex](u)^2+(u)-2=0[/tex]

Complete  the square

[tex]u^2+u=2[/tex]

[tex]u^2+u+1/4=2+1/4[/tex]

[tex]u^2+u+1/4=9/4[/tex]

rewrite as perfect squares

[tex](u+1/2)^2=9/4[/tex]

square root both sides

[tex](u+1/2)=\pm\frac{3}{2}[/tex]

[tex]u=(-1/2)\pm\frac{3}{2}[/tex]

[tex]u=(-1/2)+\frac{3}{2}=1[/tex]

[tex]u=(-1/2)-\frac{3}{2}=-2[/tex]

the solutions are

u=-2,u=1

Alternative Method

The formula to solve a quadratic equation of the form

[tex]ax^{2} +bx+c=0[/tex]

is equal to

[tex]x=\frac{-b\pm\sqrt{b^{2}-4ac}} {2a}[/tex]

in this problem we have

[tex](u)^2+(u)-2=0[/tex]

so

[tex]a=1\\b=1\\c=-2[/tex]

substitute in the formula

[tex]u=\frac{-1\pm\sqrt{1^{2}-4(1)(-2)}} {2(1)}[/tex]

[tex]u=\frac{-1\pm\sqrt{9}} {2}[/tex]

[tex]u=\frac{-1\pm3} {2}[/tex]

[tex]u=\frac{-1+3} {2}=1[/tex]

[tex]u=\frac{-1-3} {2}=-2[/tex]

the solutions are

u=-2,u=1

Find the solutions of  the original equation

For u=-2

[tex]-2=(x+3)[/tex] ----> [tex]x=-2-3=-5[/tex]

For u=1

[tex]1=(x+3)[/tex] ----> [tex]x=1-3=-2[/tex]

therefore

The solutions of the original equation are

x=-5 and x=-2

Answer:

Part 1 is x + 3

Part 2 is B u2 + u - 2 + 0

Part 3 is (u + 2)(u - 1) = 0

Part 4 is x = -5 or x = -2

Step-by-step explanation:

on edg... Good Luck!!!

ACCESS MORE